Empirical research in banking and corporate finance - Ferris, Stephen P.; John, Kose; Makhija, Anil K. (Advances in financial economics, 2022)
Empirical Research in Banking and Corporate Finance is the 21st volume of Advances in Financial Economics and deals with International Corporate Governance. Explored in detail are the role of corporate cultures, social responsibility, stock liquidity, securitization, leveraged buyouts and the cost of private debt.